Model Perlindungan dan Pemberdayaan Kaum Difabel di Kabupaten Semarang - Nisai, Rahma Amalia (LP2M Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
The protection and empowerment of people with disabilities is a crucial effort to ensure the fulfillment of basic rights and the opportunity to participate equally in social life. In Islam, every individual has equal dignity and has the right to be treated fairly without discrimination. Islamic values such as musawah (equality), i'tidal (justice), and tasamuh (tolerance) serve as the normative foundation for supporting the protection and empowerment of people with disabilities. This community service activity was carried out using a descriptive, participatory approach involving the local government, groups of people with disabilities, and the local community. The objective of this activity was to describe and support the implementation of policies and programs for the protection and empowerment of people with disabilities in Tengaran District, Semarang Regency, while also identifying concrete steps to achieve a more inclusive life. The results of the activity indicate that the empowerment efforts undertaken by the Tengaran Disability Group and the community have been successful, including through sewing skills training, a ready-to-eat, nutritious, healthy meal program, and the provision of employment opportunities for people with disabilities.